Towards the development of WirelessHART adaptor for process control applications - Supramaniam, T. (Institute of Electrical and Electronics Engineers Inc., 2017)
Recent advances in wireless technologies have prompted the applications of these cheap technologies to industrial monitoring and control application. However, this application is hindered by lack of adequate infrastructure such as the wireless adaptors. This led to the development of adaptors by organization such as Emerson Process Management, AwiaTech Corporation, etc. The developed adaptors by these organizations are expensive and not easily interoperable with devices from other manufacturers. To overcome this problem, this work proposes development of a low cost and interoperable adaptor. The adaptor will be developed around a wireless mote and a microcontroller. Preliminary results show that it is possible to perform two level control with the adaptor as shown from the experiment. © 2016 IEEE.